Scratching the discs: Evaluating alternative hypotheses for the origin of the Ediacaran discoidal structures from the Cerro Negro Formation, la Providencia Group, Argentina - Inglez, Lucas [UNESP]; Warren, Lucas V. [UNESP]; Quaglio, Fernanda; Netto, Renata G.; Okubo, Juliana [UNESP]; Arrouy, Maria J.; Simões, Marcello G. [UNESP]; Poiré, Daniel G. (Cambridge University Press (CUP), 2021)
In the Ediacaran marine succession of the Cerro Negro Formation (Tandilia System, NE Argentina), abundant microbially induced sedimentary structures indicate general conditions of substrate biostabilization. Numerous discoidal structures in this succession were previously interpreted as moulds of soft-tissue holdfasts of sessile organisms, within the form genus Aspidella. In this study, we performed a detailed re-analysis of some of these features and discuss two alternative hypotheses to explain their genesis: (1) as the result of soft-sediment deformation and fluid injection structures; and (2) as structures of active animal-sediment interaction (i.e. trace fossils). We show that the dome-shaped discs are internally laminated, with a cylindrical to a funnel-shaped vertical tube at their central region. The presence of these downwards vertical extensions and other intricate internal arrangements cannot be explained under the taphonomic spectrum of discoidal fossils, but shows striking similarities to Intrites-like structures and other sand-volcano-like pseudofossils (e.g. Astropolithon). However, some structures are hard to distinguish from vertical dwelling burrows with funnel-shaped apertures and thick-lined walls, commonly produced by suspension- and detritus-feeding invertebrates (e.g. Skolithos isp., Monocraterion isp. and, less likely, Rosselia isp.). Since reliable age constraints are unavailable, and further investigation concerning other palaeobiological indicators is needed, the most parsimonious hypothesis is that of a structure derived from fluid-escape processes. Our study demonstrates the importance of detailed investigation on discoidal structures in either upper Ediacaran or lower Cambrian strata.
Keywords: Aspidella-plexus; Ediacaran biota; Keywords; soft-sediment deformation; vertical burrows